Linguistics Pattern on Acehnese Reduplicative System: Classifications and Meanings - Ika Apriani Fata; Bukhari Daud; Lussi Maunira; Eka Wahjuningsih (OKARA: Jurnal Bahasa dan Sastra, 2022)
The significance of reduplication in language studies was to construct a linguistics pattern. However, linguists tend to disregard the functions of individual creativity and the core language meaning-making approach at the discourse level. Therefore, we should investigate this intriguing topic more to describe the repetition of words. Many studies analyzed classification reduplication in Acehnese through documentation techniques, in contrast, this current study investigated classifications and meanings of reduplication in Acehnese through observation and interview. Sulaiman's paradigm as the framework stated that reduplication had three parts: complete, affix, and ablaut reduplication. In addition, the researchers used the Ali et al. framework, which suggested eight meanings of reduplication, mainly grammatical meanings. The findings revealed that full reduplication was the most common among the 100 data of utterances. Furthermore, the meanings of reduplications are to convey the collective and distributive meaning, to express resemblance, and to express simultaneously and continuously were not discovered. The current study looked at how people could use morphological perspectives on reduplication in community discussions. Acehnese reduplication may vanish.